PENGARUH KEMAMPUAN, SIKAP DAN KECERDASAN EMOSIONAL TERHADAP EFEKTIVITAS KERJA PEGAWAI DINAS PARIWISATA DAN EKONOMI KREATIF PROVINSI RIAU - Mohd Anugrah Fikrie; Jumiati Sasmita; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the Office of Dinas Pariwisata Dan Ekonomi Kreatif Provinsi Riau Jl. General Sudirman 200 Pekanbaru - Riau. The purpose of this study was to analyze the influence of ability, attitude and emotional intelligence to the effectiveness of the staff of Department of Dinas Pariwisata Dan Ekonomi Kreatif Provinsi Riau. The study population was 93 employees of the Dinas Pariwisata Dan Ekonomi Kreatif Provinsi Riau.Variable research is the ability, attitude and emotional intelligence as an independent variable and the effectiveness of the employee as the dependent variable. Methods of data analysis using multiple linear regression analysis aided by SPSS 20 for windows. The results of this study concluded that the ability, attitude and emotional intelligence in partial and simultaneously have a significant influence on the effectiveness of the staff of Dinas Pariwisata Dan Ekonomi Kreatif Provinsi Riau. Where is the most dominant factor affecting the effectiveness of the work is the attitude factor. Research that has been conducted in accordance with the regression test (t test) and (f test) shows the independent variables studied were variable abilities, attitudes and emotional intelligence has a significant effect on the dependent variable employee effectiveness.Keywords: Ability, Attitude And Emotional Intelligence and Effectiveness of work